2012
DOI: 10.1016/j.rpor.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neoadjuvant oral chemotherapy with UFT plus Folinic acid or Capecitabine concomitant with radiotherapy on locally advanced rectal cancer

Abstract: Patients treated with neoadjuvant oral UFT + Folinic acid had a higher rate of pathologic complete response than patients treated with Capecitabine concomitant with radiotherapy. There were no differences in downstaging, LRR, toxicity, survival or loco-regional control between both groups. There was a trend to a higher rate of toxicity to adjuvant chemotherapy in the Capecitabine group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The result of our SA-2 was in line with the literature in that the OS was similar in both groups (7). In fact, another oral fluoropyrimidine anticancer agent (S1) was also reported to have similar effectiveness as capecitabine in another CER (20).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result of our SA-2 was in line with the literature in that the OS was similar in both groups (7). In fact, another oral fluoropyrimidine anticancer agent (S1) was also reported to have similar effectiveness as capecitabine in another CER (20).…”
Section: Discussionsupporting
confidence: 89%
“…We did not find any head-to-head randomized studies comparing UFT and capecitabine in 91 search results, although an under-powered North American randomized study showed that UFT had similar survival rates but lower toxicity outcomes than intravenous FU (8). We also found the above-mentioned moderately sized (n=112) European comparative effectiveness research (CER) (7) and other CERs that compared a UFT regimen to an intravenous chemotherapy drug regimen (9,10). Given the limited evidence on this issue, we investigated the relative effectiveness of UFT and capecitabine in NCCRT for LARC patients via a propensity score (PS)-matched analysis among an Asian population.…”
mentioning
confidence: 99%